Aktivitas antioksidan kombinasi ekstrak rumput laut merah (Eucheuma cottonii) Sumbawa dan ekstrak kulit buah jeruk lemon (Citrus lemon. L) impor - Dwi Kurniawati Sambodo (Jurnal Ilmiah Farmasi, 2019)
Background: The high exposure to free radicals currently has a negative impact on the health and aesthetics of the skin, especially facial skin, because it is directly exposed to the environment without any protection like the rest of the body. The human body needs antioxidants in sufficient quantities to reduce the negative effects of free radicals. Eucheuma cottoniiand Citrus lemon. L have potential bioactive compounds as antioxidants.Objective: This study was conducted to determine the antioxidant activity of combination  Eucheuma cottoniiSumbawa methanol extract (EMECS) and import Citrus lemon.L peel  methanol extract (EMCLI) Method: Antioxidant activity testing uses  DPPH method with DPPH color reduction and IC50 parameters Results: A single methanol extract of ECS, CLI, and a combination of EMECS: EMCLI (1: 1; 2: 1; 1: 2) has antioxidant activity as indicated by the fading color of DPPH solution, and IC50 single ECS and CLI extract of 942,438 ppm and 472,335 ppm, while for the combination of EMECS: EMCLI (1: 1; 2: 1; 1: 2) has a value of 436,607 ppm; 500,094 ppm; 345,514 ppm. Combination Index EMECS: EMCLI (1: 1; 2: 1; 1: 2) in a row of 0.59630; 1,43246; 0.46942 which shows a synergistic effect; intermediate antagonist; and synergistic for the combination of the two extracts.Conclusion: From this study, a combination of Sumbawa Eucheuma cottoniiextract and Citrus lemon . L import extract has antioxidant activity, with 2 comparisons having a synergistic effect (1: 1, 1: 2) and 1 comparison with intermediate antagonistic effects (2: 1).Keywords : antioxidant activity, Eucheuma cottonii. L, Citrus lemon. L, DPPH, IC50